Performance Measurement Analysis Based on Baldrige Excellence Framework in Palm Oil Company - Alda, Tania (Jurnal Sistem Teknik Industri, 2021)
Performance measurement is needed to evaluate the condition of the company. Based on preliminary discussions with the company, the company's performance measurement still focused on the financial aspects and has not carried out a comprehensive performance measurement involving other aspects of the company that is also important to know its performance. So, the company does not know the substantive condition of the company. The purpose of this research is to identify the position by using the Baldrige excellence framework (BEF) so that the company knows its condition and can improve and enhance the company's performance. Baldrige excellence framework used to identify the position of the company using seven criteria, namely leadership, strategy, customers, knowledge management, workforce, operations, and results. After identifying the company's position with the baldrige excellence framework, then analysis is carried out to find the root cause of the problem based on the Baldrige Excellence Framework assessment using a fishbone diagram. The maximum score of the Baldrige Excellence Framework is 1000. Based on the assessment, the results showed that the company was in the Early Result category with a value of 314,25. It means that the company is already at a good early stage to achieve the company's excellent performance.